Proceso atención de enfermería en lactante menor con neumonía no especificada y obstrucción intestinal. - Vasquez Coello, Anyi Carolina (2022)
The purpose of the nursing care process presented is to identify the altered needs, correct, maintain and rehabilitate the patient through the application of knowledge and procedures with the purpose of recovering their health in the shortest possible time; in this case an infant diagnosed with UNSPECIFIED PNEUMONIA and INTESTINAL OBSTRUCTION. Today pneumonia is one of the main causes of death in infants, its main affectation is the pulmonary alveoli, which compromises the respiratory system. This infectious disease, if not treated promptly, can have complications such as acute respiratory failure, lung abscess, and congestive heart failure. Intestinal obstruction is a significant mechanical change or complete cessation of bowel movement due to disease that causes a blockage in the intestines. We proceed to the elaboration of the nursing care process based on the 11 functional patterns of MARJORY GORDON, an individualized care plan was designed aimed at maintaining the functional patterns for this, the following taxonomies were used: NANDA (Diagnosis), NIC (Interventions), NOC (Results).